Partnership for Health: A Case of Lapu-Lapu City - Virginia S. Pineda (Philippine Institute for Development Studies (PIDS), 1998)
This paper is one of eight case studies in the health sector conducted under the project "Population and Urbanization: Managing the Urbanization Process Under a Decentralized Governance Framework" jointly undertaken by the Philippine Institute for Development Studies, the National Economic and Development Authority and Development Academy of the Philippines. This paper is a case study on Lapu-lapu City recommended by NEDA-Region VII as a model city for health. From being one of the lowest performers in the implementation of the Expanded Program on Immunization (EPI), the city was awarded as the Most Accelerated City in EPI in 1991.
Keywords: 330; urban management; health sector